Adaptations of Cattle to Thermal and Transitional Stress-exploration of the Potent Physio-metabolic Markers: A Review - Vaidya, Mangesh; Wankar, Alok; Kuralkar, Prajkta; Amrutkar, Suhas; Panchbhai, Girish; Wade, Mangesh; Deshpande, Kuldip; Kekan, Prakash; Ukey, Apeksha; Singh, S. V. (International Journal of Bio-resource and Stress Management, 2026)
In this review, we tried to align the physio-metabolic changes in dairy cattle during heat stress and, transition period and identify the common stress markers. Heat stress to date remainedone of the major constraints on animal welfare and production, which wasevidenced by huge production losses and high mortality. Animals have evolved different coping strategies, which included behavioral, physiological, and biochemical acclimations, oriented for acute, short-term term and long-term stress. Additionally, the transition period and lactation phase werealso stressful to the dairy cows. Monitoring these indicators couldbe very helpful to validate the animal’s stress response and the severity of stress. Animals affected form heat stress commonly have reduced feed intake and drink more water, which wascoupled with changes in behavior like seeking shade, standing more, facing away from the sun, etc. Respiratory changes like panting, variable cardiovascular response like increased heart rate, pulse rate and gradual increase in skin temperatures and core body temperature werenoted thereafter. Heat stress also modulatedand rewiredthe nervous and endocrine system, and there was a major shift in energy metabolism, resulting in higher utilization of fats, evident by high triglyceride, cholesterol and non-esterified fatty acids (NEFA) levels. Hormones like cortisol wereupregulated, and others like thyroid and insulin wereaccordingly modulated, for the cellular and metabolic stress adaptation. The literature on animal response to stress wasexpansive, but here we wouldfocus simply on the common and potent physiological and metabolic indicators, which confirmed the impact of heat and transition stress in dairy cattle.